SCABIOSA COLUMBARIA: A REVIEW OF ITS MEDICINAL USES, PHYTOCHEMISTRY, AND BIOLOGICAL ACTIVITIES: ETHNOPHARMACOLOGY OF SCABIOSA COLUMBARIA - ALFRED MAROYI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Scabiosa columbaria is a perennial herb widely used as herbal medicine throughout its distributional range in tropical Africa, Asia, and Europe. This study is aimed at providing a critical review of the biological activities, phytochemistry, and medicinal uses of S. columbaria. Documented information on biological activities, medicinal uses, and phytochemistry of S. columbaria was collected from several online sources which included BMC, Scopus, SciFinder, Google Scholar, ScienceDirect, Elsevier, PubMed, and Web of Science. Additional information on the biological activities, phytochemistry, and medicinal uses of S. columbaria was gathered from pre-electronic sources such as book chapters, books, journal articles, theses, and scientific publications sourced from the university library. This study showed that the aerial parts, leaves, roots, stems, and the whole plant parts of S. columbaria are used as colic, love charm and for magical purposes, and as herbal medicine for eye problems, heartburn, respiratory problems, wounds, female infertility, venereal diseases, skin infections, and menstrual problems. Phytochemical compounds identified from the aerial parts and roots of S. columbaria are glycoside scabiosin, loganin, sweroside, palmitic acid, phthalic acid, diisooctyl phthalate, bis-(ethylhexyl) phthalate, and dibutyl phthalate. Pharmacological research revealed that S. columbaria extracts and compounds have antibacterial, antifungal, and antiprotozoan activities. Future research should focus on evaluating the phytochemical, pharmacological, and toxicological properties of S. columbaria crude extracts as well as compounds isolated from the species.